T follicular helper cells and T follicular regulatory cells in autoimmune diseases - Qi, Jingjing; Liu, Chang; Bai, Ziran; Li, Xia; Yao, Genhong (Frontiers in Immunology, 2023)
T follicular helper (Tfh) cells are heterogeneous and mainly characterized by expressing surface markers CXCR5, ICOS and PD-1, cytokine IL-21, and transcription factor Bcl6. They are crucial for B cell differentiation into long-lived plasma cells and high-affinity antibody production. T follicular regulatory (Tfr) cells were described to express markers of conventional T regulatory (Treg) cells and Tfh cells, and able to suppress Tfh cell and B cell responses. Evidence has revealed that the dysregulation of Tfh and Tfr cells is positively associated with the pathogenic processes of autoimmune diseases. Herein, we briefly introduce the phenotype, differentiation and function of Tfh and Tfr cells, and review their potential roles in autoimmune diseases. In addition, we discuss the perspectives to develop novel therapies targeting Tfh/Tfr balance.